Variabel-Variabel yang Mempengaruhi Penurunan Pendapatan Pelaku Usaha di NTT Akibat Pandemi Covid-19 - Dina Nur Rahmawati; Artha Lucya Siahaan (Badan Pusat Statistik Provinsi NTT, 2021)
The Covid-19 pandemic has devastated regional and global economy, including Indonesia and NTT. The Central Bureau of Statistics as a state institution providing statistics responded to the Covid-19 pandemic by taking part in providing data through the Covid-19 Impact Survey on Business Actors Volume 1 which was held on 10 - 26 July 2020 by Computer Assisted Web and Self Interviewing or Online Survey. This survey aims to provide the latest indicators of business actors affected by the Covid-19 pandemic. This study specifically aims to examine the decline in income of business actors in NTT due to the Covid-19 pandemic by using ordinal logistic regression analysis. The variables analyzed in this study are the decrease of income, business location, business scale, business field, working hour, employee constraint, raw material constraint, customer constraint, and internet usage. The result is that almost half (49,50 percent) of business actors in NTT experienced a decline in income in the “moderate” category or in the range of 21-60 percent. From the ordinal logistic regression equation, there are 5 variables that significantly influence the decline in business actors' income, there are business location, business scale, business field, customer constraint and working hour. Of the five significant variables, the variable that has a strong tendency to decrease business actors' income are working hour and business field categories.